Problematika Orang Tua dalam Melanjutkan Pendidikan Anak ke Perguruan Tinggi - Sopiani, Sopiani; Maujud, Fathul; Asyari, Akhmad; Turmuzi, Ahmad; Latif, Abdul; Ramdani, Zuhud (TAMADDUN: Jurnal Ilmu Sosial, Seni, dan Humaniora, 2025)
This study explores the challenges faced by parents in Bejelo Hamlet, Jonggat District, Central Lombok, in sending their children to higher education during the 2022/2023 academic year. Using a qualitative descriptive approach, data were collected through observations, in-depth interviews with parents, students, teachers, and community leaders, alongside documentation from schools and relevant institutions. Data analysis followed an interactive process involving data reduction, data display, and conclusion drawing. The results reveal three primary issues: (1) economic constraints, as most parents are farmers with limited income; (2) motivational factors, where some children lack the drive to continue their studies and prefer work; and (3) informational barriers, with parents having limited knowledge of higher education and scholarship opportunities. The study concludes that significant structural and cultural barriers remain in pursuing higher education. A collaborative effort among schools, local governments, communities, and families is essential to foster a more supportive educational environment. Recommendations include need-based scholarships, increased awareness of higher education, and career guidance at the secondary school level.